The impact of pension on the health behavior of elderly rural residents: evidence from China - Rui Li; Duanyang Gao; Yuying Yang (BMC Geriatrics, 2024)
Abstract Background Unhealthy behavior is an important factor threatening the health of older rural residents in China. We examine the effects of receiving pension on elderly rural residents’ health behavior (namely conscious control of sugar, salt, and edible oil intake, as well as learning health or wellness knowledge), also including effect heterogeneity by income level and gender. Methods Using China Rural Revitalization Survey (CRRS) in 2020, we used the policy rule of the China’s New Rural Pension Scheme that only those people who are over 60 years old can have access to pension as the natural experiment, and explore the causal effect of receiving pensions on the health behaviors by using regression discontinuity design method. Results Having access to pension can improve the health behavior of rural elderly residents, including increasing the probability of rural residents’ conscious control of sugar (p < 0.1) and conscious control of salt intake (p < 0.1), which is still valid after a series of robustness tests. Heterogeneity analysis finds that access to pensions is more likely to improve the health behavior of low-income families and male rural elderly residents. Conclusions The research has expanded the discussion on the correlation between the pension and the health of rural elderly residents, and the conclusion provides important policy implications for optimizing the rural elderly insurance system and leveraging pension to improve the health behavior of rural elderly residents.